THE IMPACT OF RESOURCE CAPABILITIES IN ACHIEVING THE REQUIREMENTS OF ELECTRONIC GOVERNMENT - A DESCRIPTIVE AND ANALYTICAL STUDY IN THE OF THE IRAQI MINISTRY OF HIGHER EDUCATION AND SCIENTIFIC RESEARCH - Feras Mohammed Ismail; Khalid fdhil hamad (Scholar Express Journal, 2022)
The research aims to identify the importance and role of human resource capabilities in public organizations and their effects in creating a work mechanism in a new style through the mechanism of shifting from bureaucratic work practices to electronic work mechanisms in the of the Ministry of Higher Education and Scientific Research. The questionnaire was also used as a main tool in collecting data and information from an intended community of (60) employees, including senior leaders in the ministry. A number of statistical methods were used (normal distribution test, confirmatory factor analysis, descriptive statistics, Pearson's simple correlation analysis, modeling Structural equation, path analysis, coefficient of determination R2, test (T) based on the ready-made statistical programs (spss), and the results were obtained from the applied side, which includes the interest of the Ministry of Higher Education in establishing the egovernment program through the support of management and senior leadership in developing the capabilities and skills available It has, through working to create an environment and culture, to create that flexible organizational structure that is reflected in the formation of a culture d General and variable in order to be able to perform engineering mechanisms on the mechanisms of business and operations
Keywords: Human resource capabilities; e-government